ANALYSIS OF CHEMICAL LITERACY INSTRUMENT ON OXIDATION AND REDUCTION REACTIONS MATERIAL BY USING RASCH MODEL - Eka Yusmaita; Fitri Yuliani; Fauzana Gazali (Universitas Negeri Surabaya, 2022)
This study aims to analyze the quality of chemical literacy instrument on oxidation and reduction reactions material using the Rasch model. The instrument construction is based on four domains of chemical literacy which include aspects of content, context, HOLS, and affective. The instrument assessment rubric is grouped into five levels, namely (1) scientific illiteracy, (2) nominal scientific literacy, (3) functional scientific literacy, (4) conceptual scientific literacy and (5) multi-dimentional scientific literacy. Assessment criteria for chemical literacy instrument carried out by experts include aspects of content, constructs, language and graphics consisting of thirteen sub questions. The score obtained from validation process is a type of multi-rater data which is analyzed by using the Many Facet of Rasch model. The next stage is empirical study of validated and revised instrument was tested on a limited basis to thirty students and analyzed using the Winstep application. Based on the results of the research, chemical literacy instrument is categorized as valid based on the fit test and unidimensionality test.